Identification of a STIM1 Splicing Variant that Promotes Glioblastoma Growth - Jiansheng Xie; Guolin Ma; Lijuan Zhou; Lian He; Zhao Zhang; Peng Tan; Zixian Huang; Shaohai Fang; Tianlu Wang; Yi‐Tsang Lee; Shufan Wen; Stefan Siwko; et al. (Advanced Science, 2022)
Abstract Deregulated store‐operated calcium entry (SOCE) mediated by aberrant STIM1‐ORAI1 signaling is closely implicated in cancer initiation and progression. Here the authors report the identification of an alternatively spliced variant of STIM1, designated STIM1β, that harbors an extra exon to encode 31 additional amino acids in the cytoplasmic domain. STIM1β, highly conserved in mammals, is aberrantly upregulated in glioma tissues to perturb Ca2+ signaling. At the molecular level, the 31‐residue insertion destabilizes STIM1β by perturbing its cytosolic inhibitory domain and accelerating its activation kinetics to efficiently engage and gate ORAI calcium channels. Functionally, STIM1β depletion affects SOCE in glioblastoma cells, suppresses tumor cell proliferation and growth both in vitro and in vivo. Collectively, their study establishes a splicing variant‐specific tumor‐promoting role of STIM1β that can be potentially targeted for glioblastoma intervention.